Self-Pollinated Types and Ecological Adaptations of the Desert Plant Gymnocarpos przewalskii - Jiaxin Jian; Xueping Chai; Xiaonan Zhao; Zhaoping Yang (Plants)
In desert plants, outcrossing is frequently limited by pollinator scarcity, leading to a certain percentage of self-fertilization. However, research on the ecological adaptations of self-fertilized seeds remains limited. Gymnocarpos przewalskii Maxim, a Tertiary relict plant in the arid deserts of Northwest China, exhibits pronounced self-pollination. In this study, the population of G. przewalskii from the fifth regiment of Alar City was selected to explore its self-pollination types, self-pollination percentages, and ecological adaptations. We found that artificially cross-pollinated G. przewalskii produced heavier seeds, faster germination, seedlings with greater biomass, and stronger environmental adaptability than self-pollination. However, the frequency of insect visits per flower was less than one. The fruit setting rate of natural pollination was 6.90%, while that of self-pollination was 4.43%, accounting for 64.20% of the natural fruit setting rate. Additionally, G. pzewalskii’s filaments elongated rapidly to make the anthers and stigma at the same height before flowering. These characteristics suggest that G. przewalskii is capable of autonomous self-pollination and is prior selfing. Gymnocarpos przewalskii likely produces a high proportion of the selfing merely to ensure population survival. These findings offer valuable insights into the adaptation of desert plants to the scarcity of pollinators.